Habilidades sociales en estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - López Ramos, Erika Isabel (2022)
The main goal of this research project was to analyze the development of social skills in students in first, second and third terms at Psych pedagogy career at Universidad Nacional de Chimborazo. In theory, social skills according to Flores et al. (2016), are a set of cognitive- behavioral competencies that allow human beings to have positive, assertive relationships which are favorites with other human beings. Methodologically, a non-experimental design was used, due to the type of research it was descriptive, due to the transversal time, the population was the students of Psych pedagogy career, the sample was non-probabilistic and intentional, The study population was with 114 students of first, second and third terms, the technique applied was psychometric with EHS Social Skills Scale of Elena Gismero González instrument. Moreover, it was possible to obtain the data and results, concluding that, the students can be established that the low and intermediate levels are those that predominate in the development of their social skills.